1978
DOI: 10.1017/s0043174500064572
|View full text |Cite
|
Sign up to set email alerts
|

Difenzoquat for Wild Oat(Avena fatua)Control

Abstract: Postemergence difenzoquat (1,2-dimethyl-3,5-diphenyl-1H-pyrazolium) for wild oat(Avena fatuaL.) control in spring wheat(Triticum aestivumL.), durum wheat(Triticum durumDesf.), and barley(Hordeum vulgareL.) was evaluated in the field, greenhouse, and controlled environmental chamber. Wild oat control with difenzoquat was greater at the five- that at the three and one-half or two-leaf stages of growth. Barley tolerance to difenzoquat was excellent; however, spring wheat tolerance was influenced by cultivar. Duru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
2

Year Published

1983
1983
2006
2006

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 4 publications
3
19
2
Order By: Relevance
“…For A. fatua no signi®cant dierences in glyphosate ecacy could be observed between the two relative humidity conditions used. This observation is different from that reported earlier for A. fatua treated with difenzoquat (Miller et al, 1978) and asulam (Sharma et al, 1978). For U. panicoides the reasons for the better control under the Fig.…”
Section: In¯uence Of Relative Humidity On Glyphosate Activitycontrasting
confidence: 99%
See 1 more Smart Citation
“…For A. fatua no signi®cant dierences in glyphosate ecacy could be observed between the two relative humidity conditions used. This observation is different from that reported earlier for A. fatua treated with difenzoquat (Miller et al, 1978) and asulam (Sharma et al, 1978). For U. panicoides the reasons for the better control under the Fig.…”
Section: In¯uence Of Relative Humidity On Glyphosate Activitycontrasting
confidence: 99%
“…Glyphosate ecacy was reduced under most conditions of lower soil moisture content ( Figs 1±5). This observation is similar to that reported for A. fatua using other herbicides (Jecoat et al, 1977;Miller et al, 1978;Dortenzio & Norris, 1980) and U. panicoides using glyphosate (Felton et al, 1990) but is the ®rst report of this eect using glyphosate on A. fatua. In addition, this response is identical to that seen for glyphosate in other species (Moosavi-Nia & Dore, 1979;Ismael et al, 1983).…”
Section: In¯uence Of Soil Moisture Regime On Glyphosate Activitysupporting
confidence: 89%
“…In contrast, moisture supply had no effect on the control of wild oat treated with flamprop methyl. The differences between the results reported here and those reported by Miller et al (1978Miller et al ( , 1979 probably relate to differences in experimental conditions. The fact that in the previous studies SWC was not expressed as soil water potential, i.e., as -MPa, precludes direct comparisons of the results.…”
contrasting
confidence: 96%
“…Controlled environment studies have subsequently demonstrated significant reductions in the activity of flamprop methyl (Jeffcoat et al 1977), difenzoquat (Miller et al 1978) Dortenzio and Norris (1980) and Akey and Morrison (1983) comparable reductions in activity of diclofop methyl applied to wild oat were observed. In contrast, the 6% reduction in difenzoquat activity at low SWC was much less, and the 8% reduction in flamprop methyl activity considerably greater, than reported by Miller et al (1918Miller et al ( , 1979.In Miller's experiments wild oat control with difenzoquat was reduced from 60% under high-moisture conditions to less than 25% when the plants were severely stressed.…”
mentioning
confidence: 99%
“…Surprisingly, however, triallate-resistant populations were cross-resistant to the unrelated bipyridilium herbicide, difenzoquat (O'Donovan et al, 1994;Rashid et al, 1997a). As well as being structurally dierent from triallate and EPTC, difenzoquat is applied after emergence at the 3±5 leaf stage of A. fatua (Miller et al, 1978). In Alberta, difenzoquat was not used in ®elds before A. fatua resistance was detected but, in a few cases, had been applied to control A. fatua infestations that were poorly controlled with triallate.…”
Section: Introductionmentioning
confidence: 99%